2015
DOI: 10.1016/j.ultsonch.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of the dynamics of two interacting bubbles in a megasonic field

Abstract: Clarification of the mechanism of particle removal by megasonic cleaning and control of cavitation bubbles in the megasonic field are essential for cleaning of nanodevices without pattern damage. Multiple bubble interactions complicate the mechanism of particle removal. Therefore, it is important to understand multiple bubble dynamics to clarify the mechanism of particle removal by megasonic cleaning. In the present study, the dynamics of two bubbles in a megasonic field with several initial radii and initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The secondary acoustic radiation force could be an attraction force or a repulsion force, which would depend on the distance between bubbles or the vibration of bubbles. If the attractive effect of secondary acoustic radiation force could be controlled, this powerful attraction might promote the flotation of fine particles [26] . In general, the experimental outcomes showed that the formation of carriers was related to the frequency of ultrasound, and the carriers could hardly be generated in the low-frequency USW field.…”
Section: Resultsmentioning
confidence: 99%
“…The secondary acoustic radiation force could be an attraction force or a repulsion force, which would depend on the distance between bubbles or the vibration of bubbles. If the attractive effect of secondary acoustic radiation force could be controlled, this powerful attraction might promote the flotation of fine particles [26] . In general, the experimental outcomes showed that the formation of carriers was related to the frequency of ultrasound, and the carriers could hardly be generated in the low-frequency USW field.…”
Section: Resultsmentioning
confidence: 99%
“…The cone-like bubble structure formation is a combined effect of acoustic radiation and attraction forces between the bubbles, a so-called secondary Bjerknes force. 15,16 At this low power intensity, the bubbles are seen moving towards the sonotrode. Bubble quantity decreases with distance from the sonotrode, indicating a radial gradient of acoustic pressure.…”
Section: Mechanism Of Fast Delamination By High Power Ultrasoundmentioning
confidence: 96%
“…Second, some recent experimental studies have shown that bubbles of different sizes when separated by a small distance exhibit strong nonlinear coupling [37,55,58]. Such a case was examined in Ref.…”
Section: Introductionmentioning
confidence: 99%